Gemcitabine with or without ramucirumab as second-line treatment for malignant pleural mesothelioma (RAMES): a randomised, double-blind, placebo-controlled, phase 2 trial. Issue 10 (October 2021) - Pinto, Carmine; Zucali, Paolo Andrea; Pagano, Maria; Grosso, Federica; Pasello, Giulia; Garassino, Marina Chiara; Tiseo, Marcello; Soto Parra, Hector; Grossi, Francesco; Cappuzzo, Federico; de Marinis, Filippo; Pedrazzoli, Paolo; et al.
Summary: Background: There is a preclinical rationale for inhibiting angiogenesis in mesothelioma. We aimed to assess the efficacy and safety of the anti-VEGFR-2 antibody ramucirumab combined with gemcitabine in patients with pretreated malignant pleural mesothelioma. Methods: RAMES was a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial done at 26 hospitals in Italy. Eligible patients were aged 18 years or older, had Eastern Cooperative Oncology Group performance status 0–2, and histologically proven malignant pleural mesothelioma progressing during or after first-line treatment with pemetrexed plus platinum. Patients were randomly assigned (1:1) to receive intravenous gemcitabine 1000 mg/m 2 on days 1 and 8 every 3 weeks plus either intravenous placebo (gemcitabine plus placebo group) or ramucirumab 10 mg/kg (gemcitabine plus ramucirumab group) on day 1 every 3 weeks, until tumour progression or unacceptable toxicity. Central randomisation was done according to a minimisation algorithm method, associated with a random element using the following stratification factors: ECOG performance status, age, histology, and first-line time-to-progression. The primary endpoint was overall survival, measured from the date of randomisation to the date of death from any cause. Efficacy analyses were assessed in all patients who had been correctly randomised and received their allocated treatment, and safety analyses were assessed in all patients who received at least one dose of their assigned treatment. This trial is registered with ClinicalTrials.gov, NCT03560973, and with EudraCT, 2016-001132-36. Findings: Between Dec 22, 2016, and July 30, 2018, of 165 patients enrolled 161 were correctly assigned and received either gemcitabine plus placebo (n=81) or gemcitabine plus ramucirumab (n=80). At database lock (March 8, 2020), with a median follow-up of 21·9 months (IQR 17·7–28·5), overall survival was longer in the ramucirumab group (HR 0·71, 70% CI 0·59–0·85; p=0·028). Median overall survival was 13·8 months (70% CI 12·7–14·4) in the gemcitabine plus ramucirumab group and 7·5 months (6·9–8·9) in the gemcitabine plus placebo group. Grade 3–4 treatment-related adverse events were reported in 35 (44%) of 80 patients in the gemcitabine plus ramucirumab group and 24 (30%) of 81 in the gemcitabine plus placebo group. The most common treatment-related grade 3–4 adverse events were neutropenia (16 [20%] for gemcitabine plus ramucirumab vs ten [12%] for gemcitabine plus placebo) and hypertension (five [6%] vs none). Treatment-related serious adverse events were reported in five (6%) in the gemcitabine plus ramucirumab group and in four (5%) patients in the gemcitabine plus placebo group; the most common was thromboembolism (three [4%] for gemcitabine plus ramucirumab vs two [2%] for gemcitabine plus placebo). There were no treatment-related deaths. Interpretation: Ramucirumab plus gemcitabine significantly improved overall survival after first-line standard chemotherapy, with a favourable safety profile. This combination could be a new option in this setting. Funding: Eli Lilly Italy. Translation: For the Italian translation of the abstract see Supplementary Materials section.